Bandwidth Shaping Menggunakan Proxy Squid - Dwi Yatmoko Siambudi; wamiliana .; wisnu wardhana (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2018)
The development of technology is very fast. Nowadays, technology has influenced human life. For most people, handphone and computer now become a necessity. Computer can giveÂ information as we need with internet, but internet can cause a negative influence as well. In this research, we build an web base application which can block a negative-influence sites using Squid Proxy. Squid is a daemon that used as a proxy server and web cache. It can work as a connection sharing, filtering and caching. The web which domain block is successfully built which can create a bandwidth share and domain block web base application.